The Insigth and the positioning in distributors companies of massive consumption products in Huánuco - Céspedes-Galarza, Quintidiano N. (2020)
Insigth as a business perspective, are non-tangible aspects of the way in which the consumer thinks, feels or is in his mind about the brand of products. The objective of the research was to know the incidence of intellectual, emotional and structural insight in the positioning of the mass consumption products distributed by companies in the province of Huánuco. The inductive and deductive method was used in the study of the dimensions of insight: structural, intellectual and emotional; The analytical method, allowed to have a global vision of the incidence of insight in the positioning of the products and the statistical method for the processing, analysis and interpretation of results presented in tables. Demonstrating before (pre-test) the application of the theoretical, doctrinal and practical foundations of insight, that the marketing companies had no knowledge and concern in knowing what the customer thought of the products, nor the structural part of them; When applying the experimental treatment (post test), in the commercialization of products such as: dairy products, groceries and preserves, an improvement in the cognitive, emotional and structural aspects of the products was evident, and their positioning was significantly improved. Concluding that in the product distribution companies there was no innovation in the diversified supply of products; in marketing strategies and did not use branding to build a defined brand which generated a low positioning of products in the market.